ASSOCIATION BETWEEN THE DIETARY INFLAMMATORY INDEX AND PLASMA CYTOKINES IN RECREATIONAL ROAD RUNNERS AND SEDENTARY INDIVIDUALS - Flores, Priscila da Trindade; Ribeiro, Joane Severo; Isidoro, Bruna Moraes; Peres, Alessandra (Seven Editora, 2026)
Objective: To evaluate the association between the Dietary Inflammatory Index (DII) and plasma cytokine concentrations in recreational road runners and sedentary individuals. Methods: A cross-sectional study was conducted with adult recreational runners and sedentary individuals. DII, body composition and training variables, and plasma concentrations of inflammatory cytokines were assessed. Results: Among runners, DII showed a positive association with IL-6 and IL-1β, even after adjustment for age, sex, and body fat percentage. In the adjusted models, DII remained associated with IL-6 (β = 28.4%; 95%CI: 8.5–51.2; p = 0.006) and IL-1β (β = 25.6%; 95%CI: 3.1–47.0; p = 0.021). Among sedentary individuals, the correlations observed between DII and IL-10, IL-1ra, and TNF-α did not remain significant after adjustment. Runners showed higher concentrations of IL-6 and IL-1β, whereas sedentary individuals showed higher body fat percentage and a positive association between DII and adiposity. Conclusion: The inflammatory potential of the diet was associated with the plasma cytokine profile in recreational runners, but not in sedentary individuals after adjustment. These findings suggest distinct inflammatory profiles between groups and indicate that diet quality may be related to the basal inflammatory profile in physically active individuals.